The Mahishasur Movement Online a Precarious Network of ?Demon-Followers?. - Sen, M.
This article addresses the reframing of Hindu history, mythology and rituals in a WhatsApp group as part of a larger social movement called the ?Mahishasur movement? arising from a nation-wide controversy around a religio-political ritual. It addresses the mediatized controversy that led to the movement, the creation of this particular social media network, the material circulated on it and the nature of hierarchy between different participants. Contrary to existing scholarship, the findings from my fieldwork in different parts of India show that non-elite precariat groups involved in identity politics at different levels participate in social media activism which has so far been understood as a domain of Anglophone middle classes. The article shows the possibilities and challenges generated by the participation of these non-elite political activists in rural and small town India in social activism alongside their urban counterparts on social networking sites particularly WhatsApp.